Associations between complications and health‐related quality of life in individuals with diabetes. (25th March 2013) - Venkataraman, K.; Wee, H. L.; Leow, M. K. S.; Tai, E. S.; Lee, J.; Lim, S. C.; Tavintharan, S.; Wong, T. Y.; Ma, S.; Heng, D.; Thumboo, J.
Summary Objective Type 2 diabetes and associated complications adversely affect health‐related quality of life (HRQoL). However, it is unclear whether different complications have the same or different associations with HRQoL. We examined associations between retinopathy, nephropathy, peripheral neuropathy (microvascular), coronary heart disease, stroke and peripheral arterial disease (macrovascular) in diabetes and HRQoL. Design This study was a follow‐up examination between 2004 and 2007 of participants from four previous cross‐sectional population‐based studies in Singapore. Methods Health‐related quality of life was assessed through self‐administered SF‐36 health survey version 2. Diabetes and complications status were assessed through self‐report, clinical and laboratory examinations. About 2601 individuals, 2205 healthy and 396 with diabetes, were studied. Results Lower physical component scores (PCS) were associated with microvascular (2·96 points, P < 0·001) and both macro‐ and microvascular complications (4·67 points, P < 0·001), but not diabetes alone. Coronary heart disease (3·86 points, P = 0·007), peripheral neuropathy (11·46 points, P < 0·001) and severe retinopathy (4·46 points, P < 0·001) were associated with lower PCS. The greatest reduction in scores was seen in peripheral neuropathy. Conclusions Quality of life in patients with diabetes is affected mainly by presence of complications, and not diabetes per se. Peripheral neuropathy was associated with the greatest reduction in quality of life. Improved management to prevent or delay onset of complications may reduce the effect on quality of life in patients with diabetes.